MENCIPTAKAN GEREJA RAMAH ANAK DI SEKOLAH MINGGU GEREJA BETHEL INDONESIA TABGHA TANJUNG PIAYU - BATAM - Johannes Hutabarat; Intan Suriyant; Istriana Natalia; Aplonia Bamae (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Knowing a child-friendly Church, we believe that children are an important blessing and determine the life of the church now and in the future. When we want to prepare followers of Christ who grow and know love and witness for Christ, then this movement can be determined from the lives of children.Living the ministry of the children we serve are not just there and there is no time, but socializing about something that is considered necessary and even very important when serving them. HE conveyed the partiality of the Lord Jesus to children, But Jesus said: “Let the children be, don't hinder them from coming to Me; for people like these belong to the kingdom of heaven.”The question after that is, have we provided the right and adequate and ideal things for the ministry of these children, how much is the church's involvement in seeking child-friendly services in their environment. Let's work together in terms of creating a child-friendly culture throughout the church environment while serving them and the real application and taste contained in HIS word. Children's voices that cannot be seen and heard in writing or verbally with requests, but can be given a large enough space provided by the church for their ministry.In the era of digitalization of information technology in modern times there are many advantages and additional advantages of this technology in the growth and development of children that can be used, but there are certain sides that occur vulnerabilities to these problems that need to be watched out for arising.